Association of Common Zoonotic Pathogens With Concentrated Animal Feeding Operations - Guo, Yaqiong; Ryan, Una; Feng, Yaoyu; Xiao, Lihua (Frontiers in Microbiology, 2022)
Animal farming has intensified significantly in recent decades, with the emergence of concentrated animal feeding operations (CAFOs) in industrialized nations. The congregation of susceptible animals in CAFOs can lead to heavy environmental contamination with pathogens, promoting the emergence of hyper-transmissible and virulent pathogens. As a result, CAFOs have been associated with emergence of highly pathogenic avian influenza viruses, hepatitis E virus, Escherichia coli O157:H7, Streptococcus suis, livestock-associated methicillin-resistant Staphylococcus aureus, and Cryptosporidium parvum in farm animals. This has led to increased transmission of zoonotic pathogens in humans and changes in disease patterns in general communities. They are exemplified by the common occurrence of outbreaks of illnesses through direct and indirect contact with farm animals, and wide occurrence of similar serotypes or subtypes in both humans and farm animals in industrialized nations. Therefore, control measures should be developed to slow down the dispersal of zoonotic pathogens associated with CAFOs and prevent the emergence of new pathogens of epidemic and pandemic potential.